Outcomes of Elective Induction of Labor Versus Expectant Management - Eishah Ghaffar, Abdul Aleem Bhatti, Muqaddas Maqbool, Noor Nishan, Maryam Shahid, Sohaib Arif (Pakistan Journal of Medical & Health Sciences, 2022)
Summary Context: Both medical and nonmedical interventions to hasten labour and delivery are on the rise. Whether or not elective induction of labour improves outcomes or merely leads to additional complications and healthcare expenditures is a contentious topic in the scientific literature. Purpose: Choosing to induce labour artificially vs waiting for the baby to come naturally is the focus of this research. Data Sources: Internet, previous systematic reviews, and databases including MEDLINE (2022), Web of Science (2022), CINAHL (2022), and the Cochrane Central Register of Controlled Trials (2022). Data Extraction: Structure, patient characteristics, quality standards, and outcomes like as caesarean section and maternal and neonatal morbidity were abstracted by two writers. Data Synthesis: In all, more than a hundred publications were considered, but only 36 were included (11 RCTs and 25 observational studies). In a non-significant trend, women who were treated as if they were about to give birth (OR, 1.21 [CI, 1.01 to 1.46]) had a higher chance of having a caesarean section than women who were treated as though they were still in the early stages of pregnancy (OR, 1.73 [CI, 0.67 to 4.5]). Amniotic fluid was more likely to be meconium-stained in women who were expectantly managed than to those who had chosen to be induced (OR, 2.04 [CI, 1.34 to 3.09]). Exponential likelihood ratio = 2.04 [95% confidence interval = 1.34 to 3.09]). Conclusion: RCTs imply that inducing labor at 41 weeks or later reduces the risk of caesarean birth and meconium-stained amniotic fluid. Future research should evaluate elective induction of labor where most obstetric care is offered.